StoryCorps animated shorts [videorecording (DVD)] - Isay, David; Rauch, Tim; Rauch, Mike (PBS Distribution, 2012)
Based on the StoryCorps series on NPR which was started by former documentary filmmaker Dave Isay 2003. The shorts are based on 3-minute excerpts of interviews from the show.